Penerapan Hukum Pidana Terhadap Malpraktik Kesehatan di Indonesia: Tantangan dan Upaya Penegakan Hukum - Suhadi; Sutarno; Purnamo B (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The increasing number of medical malpractice cases in Indonesia has raised public concern regarding legal protection in healthcare services. The ambiguity in distinguishing between acceptable medical errors and criminally liable actions remains a critical issue in the criminal law system for healthcare. This article aims to analyze the application of criminal law in medical malpractice cases in Indonesia and explore the obstacles and regulatory improvements needed. This study employs a normative juridical approach with descriptive-qualitative methods, based on an examination of legislation, court decisions, and academic literature. The findings reveal that current regulations fail to provide comprehensive legal certainty, particularly in proving elements of negligence, appointing objective medical experts, and protecting medical professionals from criminalization. The discussion highlights the need for more structured technical guidelines and revisions to laws governing medical practice. The conclusion of this research asserts that the criminal law system in healthcare must be strengthened through regulatory reform, legal education for medical personnel and the public, and improved coordination between professional bodies and law enforcement authorities to achieve balanced justice